2006
DOI: 10.1016/j.jacc.2006.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Saturated Fat Impairs the Anti-Inflammatory Properties of High-Density Lipoproteins and Endothelial Function

Abstract: Consumption of a saturated fat reduces the anti-inflammatory potential of HDL and impairs arterial endothelial function. In contrast, the anti-inflammatory activity of HDL improves after consumption of polyunsaturated fat. These findings highlight novel mechanisms by which different dietary fatty acids may influence key atherogenic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
3
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 28 publications
(22 reference statements)
9
104
3
4
Order By: Relevance
“…The anti-inflammatory/ oxidative properties of HDL in the postprandial state have been studied earlier in two relatively small studies with healthy subjects. Nicholls et al (2006) showed that the anti-inflammatory potential of HDL was reduced after consumption of saturated fat and improved following the consumption of polyunsaturated fat. Patel et al (2009) demonstrated an impaired anti-inflammatory capacity of HDL in response to 20% intralipid.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory/ oxidative properties of HDL in the postprandial state have been studied earlier in two relatively small studies with healthy subjects. Nicholls et al (2006) showed that the anti-inflammatory potential of HDL was reduced after consumption of saturated fat and improved following the consumption of polyunsaturated fat. Patel et al (2009) demonstrated an impaired anti-inflammatory capacity of HDL in response to 20% intralipid.…”
Section: Discussionmentioning
confidence: 99%
“…Because vegetable oils are generally considered healthier alternatives than animal fats, this suggests that the estimates based on cohort studies may be closer to the true effects. In addition to effects on TC/HDL-C, ApoB/ApoAI, Lp(a) and CRP, cisunsaturated fats in vegetable oils may have beneficial effects on other pathways related to cardiovascular risk, such as insulin sensitivity (Summers et al, 2002;Paniagua et al, 2007) and endothelial function (Perez-Jimenez et al, 1999;Nicholls et al, 2006), in comparison with animal fats. Some vegetable oils (for example, soybean oil) also contain omega-3 fatty acids (alpha-linolenic acid), which may further contribute to the lowering of CHD risk independently of effects on blood lipids, lipoproteins or CRP (Mozaffarian, 2005).…”
Section: Degree Of Adjustment Prospective Studymentioning
confidence: 99%
“…It would therefore seem logical that the use of animal nutrition strategies to produce milk with reduced SFA and increased cis-MUFA or cis-PUFA (Chilliard et al, 2000;Givens and Shingfield, 2006) should initially be targeted at cheese and butter production. That said, there is an urgent need for robust intervention studies to evaluate the impact of such changes in a whole diet context using modern functional makers of CVD risk such as endothelial function (Nicholls et al, 2006). There is also a need for more data on the relationship between milk consumption and dementia.…”
Section: Milk Dairy Products and Chronic Disease: Conclusionmentioning
confidence: 99%